EFFECT OF SERVICE QUALITY, SUPERVISION AND CONSULTATION ON TAXPAYER COMPLIANCE - Rustina Rustina; Eldi Manca; Andi Asirah (Universitas Patria Artha, 2020)
This study aims to examine and analyze the influence of service quality, supervision and consultation on taxpayer compliance. This type of research uses explanatory quantitative research. Samples were obtained by random sampling and using accidental sampling method. Methods of collecting data through questionnaires, then the data were analyzed using multiple linear regression using SPSS. the results of this study indicate that the variable service quality does not significantly influence, while the supervision and consultation variables significantly influence the compliance of individual taxpayers.